THE TRANSFORMATION OF RELIGIOUS AUTHORITY AMONG MUSLIMS AMID DIGITAL TECHNOLOGICAL DEVELOPMENT: A SYSTEMATIC REVIEW - Saipul Umar; Siti Inayatulloh; Dewi Afriani Faradilah; Ahmad S Moussalli (Universitas Islam Depok, 2026)
The emergence of digital technology has profoundly reconfigured the landscape of Islamic religious authority, dismantling centuries-old institutional hierarchies and enabling new actors to claim epistemic legitimacy outside traditional scholarly networks. This study presents a systematic review of peer-reviewed literature published between 2021 and 2024 to examine the nature, scope, and implications of this transformation. Drawing on 40 empirical and theoretical publications sourced from SCOPUS-indexed and peer-reviewed journals, the review identifies six major thematic clusters: (1) the fragmentation of traditional religious authority structures; (2) the rise of digital da'wah and online fatwa issuance; (3) shifting patterns of youth and millennial religiosity in digital environments; (4) the role of social media algorithms in mediating Islamic discourse; (5) institutional adaptation by established Islamic bodies; and (6) emergent trust crises linked to anonymity and misinformation online. The review reveals that digitalization functions simultaneously as a democratizing and destabilizing force expanding access to Islamic knowledge while eroding established verification mechanisms that historically guaranteed scholarly integrity. Findings indicate that while traditional ulama retain symbolic authority, the criteria by which Muslims assess religious credibility have shifted toward aesthetic, relational, and algorithmic dimensions. The study contributes a conceptual typology of digital religious authority and calls for interdisciplinary frameworks that bridge Islamic jurisprudence, media studies, and sociology of religion to address the governance challenges posed by unregulated online Islamic discourse.